ОНКОЛІТИЧНА АКТИВНІСТЬ ОРТОПНЕВМОВІРУСУ ЛЮДИНИ В ЛІНІЯХ ЗЛОЯКІСНИХ КЛІТИН - Aziz, I.M.; Bhat, R.; Farrag, M.A.; Almajhdi, F.N. (PH Akademperiodyka, 2023)
Oncolytic virotherapy is an emerging biotherapeutic platform for selectively infecting cancer cells and triggering apoptosis in a number of malignant cells due to robust viral replication. Studies related to the oncolytic activity of human orthopneumovirus (hOPV) are conflicting. Aim: This study was designed to elucidate the possible role of hOPV in the modulation of cell growth and apoptosis in cancer cell lines including human epidermoid carcinoma (HEp-2), lung epithelial cell line (A549), and breast cancer cell line (MCF-7). Materials and Methods: The oncolytic activity of hOPV on cancer cells was studied in vitro. The virus titers were determined by tissue culture infectious dose (TCID50/mL) in A549 cell. The cytotoxic effect of the virus on HEp-2, A549, and MCF-7 was determined using MTT and trypan blue dye exclusion test assays. hOPV in the infected cells was detected using real-time reverse transcription polymerase chain reaction (rRT-PCR) and indirect immunofluorescence (IIF) assays. The relative expression of apoptosis-related genes (CASP-3, -8, -9, Bax, Bcl-2, Bcl-XL, TP53, P21) during virus infection was estimated using rRT-PCR assay in comparison with the house-keeping gene (GAPDH). Results: hOPV infection inhibited the growth of HEp-2, A549, and MCF-7 cells in a dose-and time-dependent manner. At a multiplicity of infection (MOI) of 5, hOPV reduced the viability of A549 cells to about 16%, HEp-2 to 22%, and MCF-7 to 28% (p = 0.001), while no significant inhibitory effect was observed when cells were infected at MOI of 1 and 2. hOPV mRNA and antigens were detected in infected HEp-2, A549, and MCF-7 cells by RT-PCR and IIF. Upon hOPV infection, expression of CASP-3, -8, -9, as well as Bax, TP53, and p21 mRNA increased while expression of Bcl-2, Bcl-xL anti-apoptotic genes decreased. In hOPV-infected A549 cells, the fold increase of CASP-8 and CASP-9, Bax, TP53, and P21 expression exceeded significantly compared to that in HEp-2 or MCF-7 cells. Conclusions: Our results provide evidence that hOPV could be a potential candidate for oncolytic virotherapy.